LiDAR-based sensor fusion and navigation for indoor autonomous mobile robots in warehouse environments - Rifda Hakima Sari; Jazi Eko Istiyanto; Oskar Natan; Zaidan Hakim; Danang Lelono; Andi Dharmawan (Institute of Advanced Engineering and Science, 2026)
An indoor navigation system for an autonomous mobile robot was developed using LiDAR-based perception and multi-sensor fusion. The system combines 2D LiDAR, inertial measurement unit (IMU), and wheel encoder measurements within a simultaneous localization and mapping (SLAM) framework to support real-time localization, while the ROS2 Nav2 stack manages global path planning and local obstacle avoidance through A*-based planning and costmap-driven control. Evaluation in a warehouse-like environment showed that the robot maintained stable localization with low drift and completed autonomous navigation missions with a success rate of 93.33%. During operation, the robot was able to avoid static obstacles consistently and adjust its trajectory in response to simple dynamic obstacles through online replanning. These results indicate that the proposed system is suitable for practical indoor logistics scenarios requiring reliable navigation in structured environments. At the same time, the findings suggest the need for further improvement to handle environments with higher dynamics and denser obstacle configurations.